Financial Development, Exchange Rate Regimes, and Growth Dynamics - Kassa, Woubet; Lartey, Emmanuel K.K. (World Bank, Washington, DC, 2018)
This paper utilizes data for African countries to analyze the extent to which financial development affects the dynamics of the relationship between exchange rate flexibility and economic growth. The findings indicate that financial development exerts a positive influence on the relationship between exchange rate flexibility and GDP growth as well as total factor productivity growth. The paper also documents a positive impact of trade openness on the relationship between exchange rate flexibility and growth. Moreover, the results show a strong and positive association between exchange rate flexibility and financial development. The findings, therefore, suggest that discussions and decisions on exchange rate policy should be undertaken with consideration for structural policies that address the development of the financial sector. In addition, the paper asserts that policy makers should adopt a stance that facilitates some flexibility in exchange rates to foster development of the financial infrastructure in these economies.